The shadow world / 2. - Johnson, Jane, 1951- (Johnson, Jane, 1951- Eidolon chronicles, 2007)
Twelve-year-old Ben Arnold returns to the magical world of Eidolon to rescue his sister Ellie and help their mother battle the vile Dodman, whose power continues to grow.